PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Riha Dedi Priantana; Ade Yustian (Program Magister Akuntansi Unsyiah, 2011)
This study aims to provide empirical evidence about the effect of managerial ownership, institutional ownership, audit committee, board size, composition of the board of commissioners on the disclosure of corporate social responsibility (CSR).This research was conducted at financial companies listed in Indonesia Stock Exchange (BEI). The population of this research is all financial firms in the periods 2007-2008. Sampling was done by using purposive sampling techniques, the company that fulfilled the criteria that is revealed in the annual report and CSR GCG structure during the years of observation in the financial statements. Data collection was done by searching selected company annual report into the sample.The type of data used are secondary data. The data used is the annual report for the years 2007-2008 obtained from the Indonesian Capital Market Directory (ICMD) and the Capital Market Reference Center (PRPM). The data analysis was conducted using the help of software (software) Courses Statistics Package for Social Science (SPSS) version 17.0.The results showed that the independent variables showed individual test managerial ownership negatively affect the disclosure of CSR with a significance level of 0.008. Institutional ownership has no significant effect of CSR disclosure. The audit committee had no significant impact of CSR disclosure. The size of the board of commissioners have a significant effect on the disclosure of CSR with a significance level of 0,000. The composition of the board of commissioners have a significant effect on the disclosure of CSR with a significance level of 0.044. Test results with the same independent variables showed a significant effect partially because not all significant variables, only variables and managerial ownership, the audit committee, board size and composition of the board of commissioners who have a significant effect on the disclosure of CSR, while institutional ownership has no effect on the level of CSR disclosure significance 0.252. Keywords: CSR, Managerial Ownership, Institutional Ownership, Audit Committee, the size of the Board of Commissioners, the composition of the Board of Commissioners.